Bioprospeksi Bakteri Asal Akar Nanas (Ananas comosus L. Merr) Lahan Gambut Kayu Agung, Sumatra Selatan, sebagai Agen Biostimulan dan Bioprotektan - Erma Suryanti; Dewi Chusniasih; Muhammad Asril; Ika Agus Rini; Wulandari Putri Antika; Nadia Rahmah (Institut Pertanian Bogor, 2023)
Pineapple (Ananas comosus L. Merr) is a plant that can live well on nutrient-poor lands such as peatlands. However, plant resistance to nutrient-poor conditions is caused by symbiosis with endophytic bacteria capable of plant growth-promoting bacteria (PGPB) through biostimulant and bioprotective mechanisms. This study aims to characterize the potential of endophytic bacteria from pineapple roots from peatlands as biostimulants and bioprotective agents. Thirteen endophytic bacteria from pineapple root were characterized by their ability as biostimulants through phosphate dissolution tests using Pikovskaya media qualitatively and quantitatively, and the production of indole-3-acetic acid (IAA) upon additional 0.1% tryptophan. Furthermore, bacteria as bioprotectors were characterized by qualitative production of chitinase enzyme and antifungal tests against Fusarium proliferatum using dual culture techniques. The results showed the presence of 2 positive bacteria in all tests, namely the ANAP3 and ANAP5 isolates. ANPA3 bacteria show the highest activity in IAA production (26.3 ppm), and the highest antifungal activity in inhibiting F. proliferatum, with an inhibitory index reaching 52.6%. Meanwhile, ANAP5 is an endophytic bacterium with the highest phosphate dissolving activity, with a dissolved phosphate value of 253.5 ppm. This finding shows that some endophytic bacteria from pineapple roots on peatlands can be biostimulants and bioprotectors that can be developed as PGPB. Keywords: Ananas comosus L. Merr, endophytic bacteria, bioprotectant, biostimulant, Fusarium proliferatum